Two-Year clinical outcomes after coronary bifurcation stenting in older patients from Korea and Italy - Kim, Ju Hyeon; Franchin, Luca; Hong, Soon Jun; Cha, Jung-Joon; Lim, Subin; Joo, Hyung Joon; Park, Jae Hyoung; Yu, Cheol Woong; Lim, Do-Sun; De Filippo, Ovidio; Gwon, Hyeon-Cheol; Piroli, Francesco; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Older patients who treated by percutaneous coronary intervention (PCI) are at a higher risk of adverse cardiac outcomes. We sought to investigate the clinical impact of bifurcation PCI in older patients from Korea and Italy. Methods: We selected 5,537 patients who underwent bifurcation PCI from the BIFURCAT (comBined Insights from the Uniﬁed RAIN and COBIS bifurcAtion regisTries) database. The primary outcome was a composite of target vessel myocardial infarction, clinically driven target lesion revascularization, and stent thrombosis at two years. Results: In patients aged ≥75 years, the mean age was 80.1 ± 4.0 years, 65.2% were men, and 33.7% had diabetes. Older patients more frequently presented with chronic kidney disease (CKD), severe coronary calcification, and left main coronary artery disease (LMCA). During a median follow-up of 2.1 years, older patients showed similar adverse clinical outcomes compared to younger patients (the primary outcome, 5.7% vs. 4.5%; p = 0.21). Advanced age was not an independent predictor of the primary outcome (p = 0.93) in overall patients. Both CKD and LMCA were independent predictors regardless of age group. Conclusions: Older patients (≥75 years) showed similar clinical outcomes to those of younger patients after bifurcation PCI. Advanced age alone should not deter physicians from performing complex PCIs for bifurcation disease.